Functional-metabolic activity of neutrophils granulocytes at patients the herpetic infection - B. S. Nagoev; Z. A. Kambachokova (Журнал инфектологии)
The article is devoted to the investigation of inner neutrophil metabolism among patients with chronic herpes infection. For the investigation the nitroblue tetrazole restoration test (NST-test) was used. NST-test enables to etermine the leukocyte readiness to phagocytosis, to detect enzymatic defects of cellular immunity. As the result of the investigation among patients with chronic herpes infection the increase of NST-test indices with maximum magnitude at the high point of diseases, reduction in die period of clinical signs and return to normal feature in the period of late deconvolution was ascertained. The degree of NST-test activity depended on severity of illness, the more severe the illness the higher was the NST-test activity.